PROSES BIOSORPSI DAN DESORPSI ION Cr(VI) PADA BIOSORBEN RUMPUT LAUT Eucheuma spinosum - N. P. Diantariani; I W. Sudiarta; N. K. Elantiani (Jurnal Kimia (Journal of Chemistry), 2008)
Studies on biosorption and desorption of chromium (VI) on seaweed (Eucheuma spinosum) biosorben havebeen carried out. These studies included determination of biosorben acidity, optimum pH, contact time ofbiosorption, isoterm and biosorption capacity, and mechanisms of interaction between chromium (VI) and seaweed(Eucheuma spinosum) biosorben. Mechanisms of interaction were known with desorption chromium (VI) onseaweed biosorben using aquades, 1 M HCl and 0,05 M Na2EDTA.The result showed that the total acidity of seaweed biosorben was 4,1545 ± 0,3290 mmol/g, the optimum pHwas 5, and the contact time was 120 minute. Biosorption capacity of seaweed (Eucheuma spinosum) to chromium(VI) was 13,4992 mg/g. The highest desorption of chromium (VI) occurred with the use of aquadest which was40,69%. Whereas desorption using 1 M HCl and 0,05 M Na2EDTA were 4,84% and 0,20% respectively. This caseindicated that the main interaction mechanism of chromium (VI) on seaweed was hydrogen and Van der Waals bondwhich was relatively weak.